Development of Digital Storytelling-Based Hand Puppet Media to Improve Storytelling Skills - Marisa Ana Tiara; Trisni Handayani (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2023)
This study aims to develop digital storytelling-based hand puppet media developed with the ASSURE model, learning Indonesian language material by observing characters in fictional texts in elementary schools, seeing responses, and improving the skills, and understanding of students. The subjects of this study were fourth-grade students of SDN Susukan 06, totaling 23 students in the 2023 school year.Data were collected using tests, questionnaires, interviews, observations, documentation, and field notes. The results of the study are (1) obtained the average score of expert validation with a percentage of 95% with the category